Socio-Economic Values in the Process of Spiritual Renewal and Development of Society - Khodievna, Ruzieva Rukhsora (International Journal on Orange Technologies, 2021)
SOCIO- ECONOMIC CUSTOMS IN THE PROCESS OF SPIRITUAL RENEWAL AND DEVELOPMENT OF SOCIETY In this article, substational points of socio-economic traditions, which have been learnt very little in scientific literatures, functional peculiarities, being formed of marketing system as a new value, also the matters of coordination of national and public values in socio- economic relation are introduced and discussed.